Glorious History of Marathas - Sarkar, Jadunath (Gurugram Shubhi Publications, 2025)
Maratha empire, early modern indian empire that rose in the 17th century and dominated much of the Indian subcontinent during the 18th century.
Keywords: Coronation of Shivaji